Improve Accreditation, Regulation, and Quality Standards : For Quality Care Amidst Absolute Infrastructure and Resource Constraints - World Bank Group (World Bank, Washington, DC, 2019)
Accreditation and re-accreditation requirements differ in existence, scope, and use across and within countries. These differences affect facilities and cadres of workers at all levels. Estimates approximate that less than sixty percent of developing countries require medical school graduates to pass national certification exams, a figure that drops below forty percent for Africa and Southeast Asia. Even where minimum standards exist, they can have low uptake due to a perceived or real absence of incentives (regulatory or financial) to pursue accreditation. Different capacities to pay for and devote resources to accreditation may result in gaps along the urban-rural divide in terms of the number of accredited facilities and services offered.